Vorarbeiten zu einer Königsliste Kaukasisch-Iberiens. 2. Das Zeitalter Pharasmanes ́ I. - Schottky, Martin (Anabasis. Studia Classica et Orientalia, 2013)
In the time of Augustus an Iberian king whose name is unknown sent envoys to the first princeps seeking his friendship. He may have been the son and successor of Pharnabazus II (36 BC) and the father or grandfather of Mithradates I, who died in 35 AD. A quarrel between his sons Pharasmanes and Mithradates concerning his succession was settled by Tiberius, who made the younger Mithradates the client-king of Armenia. The long, nearly 40 years lasting Iberian rule of Pharasmanes I was determined by the struggle for the supremacy over Armenia between Romans and Parthians. In these decades perished not only Mithradates, but also Pharasmanes ́ eldest son and heir Radamistus. At the end of his life the disappointed Pharasmanes opened the so-called „Caspian Gates“ (in this case: the pass of Derbend) to the savage Alans, who devastated Atropatene and Armenia. After his death shortly before 75, he was succeeded by his younger son Mithradates II, who is never mentioned in the literary sources. Only at the time of Traian ́s Parthian war we hear again of the Iberian royalty: a king of Iberia, one Mithradates III, paid hommage to the emperor. The king’s younger brother Amazaspus intended to take part in the Parthian war but died